The Influence of the Dimensions of Higher Education Service Quality on Student Satisfaction - Nasron Alfianto; Edy Suryawardana (At-Taqaddum, 2021)
The quality of service at the institution is one of the essential factors for service users. Higher education services are one of the institutions that need to be studied, the extent to which the quality of services is provided. This study examines the effect of higher education service quality on student satisfaction. This study uses a quantitative approach. The sampling technique used the slovin method. The primary data in this study were obtained from the perceptions of students who filled out and returned the questionnaire, analyzed using the multiple regression analysis techniques. The analysis and discussion results show that the dimensions of service quality (reliability, responsiveness, assurance of empathy, and physical evidence) have a positive effect on student satisfaction. It is recommended that service quality, such as reliability, responsiveness, empathy, and physical evidence, be further improved, considering that the effect is small except for guarantees.